Clinical characteristics of children with infantile epileptic spasms syndrome from a tertiary-care hospital in Dhaka, Bangladesh. Issue 3 (March 2023) - Abath, Christina Briscoe; Chandra Saha, Narayan; Hoque, Seikh Azimul; Islam, Ariful; Chowdhury, Yamin Shahriar; Ara Begum, Mosammat Shameem; Davalji Kanjiker, Tahera Sultana; Yuskaitis, Christopher J.; Harini, Chellamani; Alam, Md Badrul; Mohammed, Quazi Deen; Mazumdar, Maitreyi
Abstract: Background: We describe patient characteristics and response to initial treatment in a large case series of children presenting with infantile epileptic spasms syndrome to a tertiary-care hospital with a pediatric neurology service in Bangladesh. The purpose of the study was to add to the growing body of literature on infantile epileptic spasms syndrome in low- and middle-income countries. Methods: We enrolled 212 infants with new-onset infantile epileptic spasms syndrome (IESS) at the time of initial presentation to the National Institute of Neurosciences and Hospital (NINS) in Dhaka, Bangladesh, between January 2019 and August 2021. We collected data about seizure type and frequency, etiology, medication dosage, and available neuroimaging. Results: Median age at initial presentation to NINS was 9 months. Developmental delay and regression prior to presentation were found in 83% and 36%, respectively. Prior to their presentation at NINS, 197 (93%) patients had received anti-seizure medication to treat spasms, of whom only 8 (4%) had received standard therapy with ACTH, prednisolone, or vigabatrin. At NINS, 207 (98%) of patients received standard therapy, most frequently ACTH in 154 (73%). Median time between seizure onset to receipt of first-line therapy was 5 months. Of the 169 patients who were seen in follow-up at average of 5 weeks, 92 (54%) reported absence of clinical epileptic spasms. No serious adverse events requiring hospitalization were reported. Conclusions: This study highlights the long lead times to treatment for IESS in a low- and middle-income country, and the need for early referral of children with suspected epileptic spasms to epilepsy care centers. Highlights: Median time between epileptic spasm onset and receipt of standard therapy was 5 months in this case series of 212 infants. Hypoxic-ischemic injury was the most common presumed etiology of IESS (67%), similar to other South Asian cohorts. Future work in Bangladesh should focus on identification of barriers to early IESS identification and standard therapy.